CEO Confidence and Unreported R&D - Koh, Ping-Sheng; Reeb, David M.; Zhao, Wanli (Management Science, 2018)
We investigate whether managerial traits influence corporate decisions to provide mandatory financial disclosures. The results indicate that firms with confident chief executive officers (CEOs) are 24% more likely to report their research and development (R&D) expenditures relative to firms with cautious CEOs. Exploiting staggered, state-level regulatory shocks and changes in CEO type, we find substantial evidence that cautious CEO firms fail to report R&D expenditures. After a plausibly exogenous shock to managerial reporting liability, cautious CEO firms exhibit a 35% larger reduction in unreported R&D relative to confident CEO firms. Interestingly, confident CEO firms do not exhibit more innovation than their cautious CEO counterparts after taking into account their differing propensities to report corporate R&D. Overall, our analysis suggests that the precision or reliability of mandatory disclosures systematically varies with managerial characteristics. The Internet appendix is available at https://doi.org/10.1287/mnsc.2017.2809 . This paper was accepted by Amit Seru, finance.